Hapa: a Local Wisdom of Meher Ethnic Group on Kisar Island to Ensure Food Security - A.M. Sahusilawane; Muhammad Riadh Uluputty; Esther Kembauw; Sri Wahyuni Djoko (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2015)
Kisar is one of outside islands of Moluccas Province. The climate on the island is extreme so to guarding for food security against it Meher ethnic group use their traditional wisdom,â€hapaâ€. Hapa is a traditional farming system which is effective for the agriculture cultivication. Hapa bring a lot of hidden rationality and full support to the farmers of Meherto guard their food security that can be developed to all small islands which have the same climate. Hapa also exsists with the Meher women as mam lele her that means the giver of life for the family. Hapa and mam lele her support gender division labor.